FACTORS INFLUENCING PRODUCTIVE TRAITS OF AWASSI CROSSBREEDS IN MACEDONIA - Nikola Pacinovski1, Vladimir Dzabirski2, Koco Porcu2, Goce Cilev3, Elena Joshevska4, Milan P. Petrovic5, Zvonko Antunovic6 (My University, 2016)
factors that affect most of the production traits in crossbreeds between Awassi and Ovchepolian indigenous sheep in Macedonia. We implemented 1145 individual lactation controls in two years of production (2012 and 2013). The impact of individual factors is studied using F-test and the analyses are made using SPSS set of programs. Many factors (lactation, lambing month and number of milk controls) had highly significant impact (P<0.001) on daily milk production (morning, evening and total milk, fat percentage and fat kg) in this breed of sheep. Only fertility had no impact on any of the examined factors, with the exception of total daily milk, on which manifested with highly significant impact (P<0.01). The average milk yield in examined crossbred sheep was 109 ± 0.479 l in two years of production, while the production of milked milk was 72 ± 0.421 l for the same period of time. The length of lactation period in these sheep was average 203 ± 0.61 days, for two analysed years. In relation to the age, in second lactation sheep was determined somewhat higher daily milk yield (0.478 ±0.01 l.), compared to sheep in first lactation (0.475 ± 0.01 l.). This is quite logical, keeping in mind the lactation curve in sheep, especially those of dairy breeds to which Awassi breed belongs.
Keywords: Awassi crossbreeds, production traits, impact of factors, daily milk yield